Unveiling the Chemotherapeutic Potential of Novel Platinum II and Platinum IV Complexes in Skin and Breast Cancers: In Vitro and In Vivo Insights - Slika, Amjad (2024)
Thesis (M.S.) -- Biological Sciences, May 2024